Business Model Canvas: Airbag Phone Case / Muhamad Akmal Abdullah Zawawi - Abdullah Zawawi, Muhamad Akmal (2020)
This report has been dedicated to discuss the business canvas model of Airbag Phone Case. In this regard, the key partners of the business have been discussed and the key services include the manufacturing, assembly and distribution of company’s product. The company is creating value through provision of latest technology products and by handling customer’s needs and complaints. The company distributes its products with the help of different retail stores, retail outlets and online stores. It is operating with many sources amongst them; the key resources are the people who are employees of the company, its physical assets and intellectual properties